The impact of amblyopia on visual motor function, coordination, and motor skills of children and adolescents: A hospital-based cross-sectional study from North India - Mittali Khurana; Anupam Singh; Prateek Kumar Panda; Indar Kumar Sharawat; Sanjeev Kumar Mittal; Omna Chawla; Barun Kumar (Journal of Clinical Ophthalmology and Research)
Objective: To study the impact of amblyopia on visuomotor function, coordination, gross, and fine motor skills in children and adolescents aged between 4 and 18 years. Materials and Methods: A total of 82 participants, aged 4–18 years, were included in the present prospective, cross-sectional study. Age-appropriate standardized tests were used to assess and compare fine motor skills, visual acuity, and binocular vision in a subset of amblyopic children and adolescents under binocular conditions with the healthy control group. Results: Out of 82 participants, the mean age of 55 amblyopes was 9.11 + 4.06 (range, 4–18 years) and of controls was 8.44 + 3.69 (range, 4–17 years). The mean and standard deviation (SD) of the visual motor control tasks, upper limb dexterity, and visuospatial constructional ability tasks in the amblyopia versus control group were as follows: 6.73 + 4.19 (range, 0–13 score) versus 1.33 + 1.75 (range, 0–8) out of maximum 13 scores, 164.14 ± 96.26 versus 85.98 ± 29.56 s, and 22.03 ± 10.61 versus 30.15 ± 4.24 out of 36 maximum scores, which were statistically significant. The amblyopia group also had poor visual motor coordination when compared to the control group (mean and SD of 56.04 ± 10.44 vs. 61.7 ± 7.2, out of 75 maximum scores), which was statistically significant. Conclusion: Amblyopia adversely affects the fine motor skills of children and adolescents. Therefore, these patients can face difficulty in performing various tasks that require good fine motor skills. This hidden impact of amblyopia needs to be emphasized for public awareness regarding the early treatment of amblyopia during neuroplasticity.